Heat transfer performance of TiO2-SiO2 nanofluids in a tube with wire coil inserts - K., Abdul Hamid; Azmi, W. H.; R., Mamat; Sharma, K. V. (Elsevier Ltd, 2019)
The compound technique that combines nanofluids with wire coil inserts has proven itself in achieving double augmentation in heat transfer. This paper presents the thermal hydraulic performance of TiO2-SiO2 nanofluids with wire coil inserts. The experiments were conducted for Reynolds number from 2300 to 12,000 to determine the heat transfer performance and friction factor of TiO2-SiO2nanofluids with wire coil inserts. The TiO2-SiO2 nanofluids were prepared by using the two-step method for volume concentrations of 0.5–3.0%. The wire coil inserts are designed at various ratios of pitch over diameter (P/D) in the range of 0.83–4.17. The heat transfer performance of nanofluids was enhanced for a maximum of 254.4%, while the friction factor was obtained in the range of 1.76–6.38 times higher than water/EG in a plain tube. The thermal performance factor (TPF), η for the nanofluids with wire coil inserts at all volume concentrations was observed greater than 1.0. The optimum performance of TiO2-SiO2 nanofluids with wire coil occurred at 2.5% volume concentration and 1.50 pitch ratio. At this condition, the TiO2-SiO2 nanofluids with wire coil inserts provide the highest TPF and represent the best condition for cooling system applications.